2019
DOI: 10.1158/1535-7163.mct-19-0181
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Resistance to EGFR TKIs Mediated by TGFβ1/Integrin β3 Signaling in EGFR-Mutant Lung Cancer

Abstract: Investigation of novel molecular mechanisms is essential to develop strategies to overcome acquired resistance to EGFR tyrosine kinase inhibitors (TKI). Integrin has been demonstrated as a regulator of cancer progression. The aim of this study was to identify which specific integrins are involved and regulated in acquired resistance to EGFR TKIs in EGFR-mutant lung cancer. The expression levels of integrin subunits were examined in EGFR-mutant lung cancer cells and xenograft tumors with acquired resistance to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 29 publications
(46 reference statements)
3
31
0
Order By: Relevance
“…Integrin αVβ3 expression and activation drive the intracellular signalling that promotes cancer cell survival, invasion, metastasis, angiogenesis, and self-renewal [39,41], as well as chemotherapy resistance [42,43] and radiotherapy resistance [44,45]. Several studies have reported that integrin β3 is up-regulated after EGFR-TKI treatment [46,47], consistent with our findings. More importantly, our findings add to current knowledge about how integrin β3 is upregulated in resistant tumours.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Integrin αVβ3 expression and activation drive the intracellular signalling that promotes cancer cell survival, invasion, metastasis, angiogenesis, and self-renewal [39,41], as well as chemotherapy resistance [42,43] and radiotherapy resistance [44,45]. Several studies have reported that integrin β3 is up-regulated after EGFR-TKI treatment [46,47], consistent with our findings. More importantly, our findings add to current knowledge about how integrin β3 is upregulated in resistant tumours.…”
Section: Discussionsupporting
confidence: 90%
“…Overexpression of OPN/integrin αvβ3 results in activation of downstream FAK signalling, which is a key component of the signal transduction pathways activated by integrins and has an essential role in cancer cell survival, EMT, metastasis, and stemness [49]. Several studies have shown that activation of FAK signalling is associated with EGFR-TKI resistance [46,47]. Based on our results, VS-6063 can enhance sensitivity to gefitinib in PC9GR cells.…”
Section: Discussionsupporting
confidence: 59%
“…EGFR-TKIs are the most representative class of targeted therapies. Compared with traditional chemotherapy, EGFR-TKIs effectively treat advanced NSCLC with EGFR mutations and significantly prolong the OS of those patients [23][24][25]. However, the application of EGFR-TKIs also has some certain limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor recurrence and metastasis present marked challenges to clinicians and severely affect the prognosis of patients. Approximately prolong OS of patients [29][30][31] . However, the application of EGFR-TKIs also has some certain limitations.…”
Section: Discussionmentioning
confidence: 99%